FROM CULTURE TO VIRALITY: THE SOCIAL MEDIA EFFECT ON TOURIST DESTINATION IN GREATER JAKARTA AREA - Wijaya, Nathania; Tjundawan, Amadea Graciella; Waiman, Deofigrace; Gadjuli, Nadine Christabelle (Journal of Architecture&ENVIRONMENT, 2025)
Social media platforms such as Instagram or TikTok have shifted how tourists perceive architectural designs of both local and international destinations. The clickbait-driven content and algorithms used within these platforms expose users to see similar things repeatedly, which subconsciously change people’s preferences. Builders used this opportunity to recreate “viral” places to repeat the glory of its predecessor. This research investigates how this phenomenon has shifted architectural typology, particularly within Greater Jakarta. Through a mixed method approach that blends architectural theory content analysis from social media posts, surveys, and statistical data, this study aims to investigate the rising trend of “copycat” design to attract a larger audience. Findings reveal a significant correlation between viral destinations and architectural development in greater Jakarta. While this trend potentially promotes tourism and potentially economic growth, it also sparks debate around the erosion of cultural identity and authenticity. This paper demonstrates that while the so-called “form follows Instagram” approach might work on a superficial level, it fails to embrace the deeper beauty and locality of architectural design. Furthermore, this paper aims to open a dialogue on the future of architectural expression in a media-saturated society, where likes and shares shape the built environment, where copying and pasting are seen as a mere habit.